Dealing with forty students: peer-assessment as an alternative for English teachers in Indonesia - Agus Sufyan; Didin Nuruddin Hidayat (University of Muhammadiyah Purwokerto, 2020)
English teachers in Indonesia typically teach in large classroom size, with high possibility to teach more than two classes. When it comes to assessing students’ work, most of them tended to rely on teacher assessment, for it is considered as part of their duties as professional teachers. However, when dealing with students’ work, students may also need superficial and substantial correction and feedback rather than receiving marks only. Nevertheless, to provide those corrections and feedback, English teachers need a considerable amount of time to complete the assessment process; estimated calculation has been provided in this paper. Therefore, this conceptual paper aims to provide an alternative way to assess students’ work through peer assessment. Some benefits and challenges have been discussed to give insights for English teachers in Indonesia. This paper agrees that peer assessment can help teachers regarding time efficiency and help students regarding increased learning engagement. Moreover, English teachers need to pay tackle to some challenges such as shifting from a traditional perspective towards teacher authority and addressing issues of validity and reliability from students’ marking results. This paper suggests that though teachers can minimize their workload, their presence is pivotal in assisting students during the assessment process.